Stirring the spirits in a baffled struggle for constructive AIDS politics. A report on the 'Aids in Context' conference Johannesburg 4-7 April 2001 - Ruether, Kirsten (Missionalia: Southern African Journal of Mission Studies, 2001)
The article gives an account of the 'AIDS in Context' conference held at the University of the Witwatersrand in April 2001. It adopts a postmodern approach that concentrates on fragmented narratives and the construction of knowledge through competing discourses. It gives a critical ""who's who"" of the conference which shows that a diverse spectrum of qualified people (mainly activists) participated, who took their motivation from very different backgrounds.
Free